Meningkatkan Hasil Belajar PAKBP pada Materi Manusia Berkembang Berkat Peran Sesama Menggunakan Model Problem Based Learning di Kelas VII SMP Negeri 1 Batang Kuis - Dewi Fitri Sitindaon; Yusmanto Yusmanto; Busri Busri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of seventh-grade students on the material "Human Development Through the Roles of Others" using the Problem-Based Learning (PBL) model at SMP Negeri 1 Batang Kuis. This research employed a Classroom Action Research design conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 7 students from the seventh-grade class at SMP Negeri 1 Batang Kuis. Data collection techniques were carried out through tests (formative tests) and non-tests (observations). The results of the study in cycle I showed an average score of 68.14 and a classical learning completeness percentage of 72.42%. In cycle II, the average score increased to 84.85. The average student attendance in cycle I was 100% and remained 100% in cycle II. Student involvement in learning in cycle I was 66.28% (high) and increased to 76.50% (very high) in cycle II. It can be concluded that the PBL model can improve the learning outcomes and activities of students on the material "Human Development Through the Roles of Others" in the seventh-grade class at SMP Negeri 1 Batang Kuis.